Distribution and sources of organic carbon, nitrogen and their isotopic composition in surface sediments from the southern Yellow Sea, China. (January 2020) - Liu, Xingjian; Tang, Dehao; Ge, Chendong
Abstract: The southern Yellow Sea (SYS) is a significant repository of sedimentary organic matter (SOM) and has been impacted by green tides since 2007; however, data on the distribution and quantitative contributions of different SOM sources has been scarce. TOC, TN and their δ 13 C and δ 15 N values were determined in 38 surface sediments. TOC and TN were high in central mud area and low in sand area. TOC was positively correlated with the abundance of fine-grained sediments, indicating that controlling factors of SOM were the sediment types and circulation system. The SOM included marine and terrestrial organic matter and anthropogenic nutrient inputs according to TOC/TN (5.8–14.3), δ 13 C (−25.1‰ to −21.0‰) and δ 15 N (2.6‰–6.4‰). High terrestrial contributions in northern and western parts of SYS, were influenced by terrestrial materials and eroded substances of the abandoned Yellow River delta, respectively. In the central mud area of SYS, marine organic matter was dominant. Graphical abstract: Unlabelled Image Highlights: Terrestrial and marine organic matter, anthropogenic nutrient inputs are sources. Marine organic matter was the dominant source in the SYS shelf sediments. High terrestrial contributions were influenced by abandoned Yellow River substances. The circulation system and sediment composition controlled distribution of TOC. High TOC and TN concentrations were found in the central mud region.